Influence of some additives on burning rate of KNO3-based compositions - Tuan, Nguyen Duy; A. P., Denisuyk; Khai, Doan Minh; V. A., Sizov (Vietnam Journal of Science and Technology, 2023)
In this article effect of some additives on combustion behaviour of high energetic compositions based on KNO3 was studied. The KNO3-based samples were made by mixing, rolling, and pressing. Investigated additives were: copper salicylate, nickel salicylate, copper-lead phthalate, nickel-lead phthalate, soot and carbon nanotubes. Burning rate was determined by the pressure increasing by using modification of the corner point method. It is shown that individual additives insignificantly effect on the burning rate of studied samples. The carbon nanotubes brand TMD with specific surface area ~270 m2/g and copper salicylate are the most effective additives on the burning rate. It should be noted that copper salicylate with carbon nanotubes have a significantly greater effect on the burning rate than individual additives or the catalyst with soot.